Comparison of Surgically Induced Astigmatism by Superior and Temporal Clear Corneal Incision in Phacoemulsification - Asif, Muhammad; Malik, Aqsa; Muneer, Madasar (Biological and Clinical Sciences Research Journal, 2025)
Cataract surgery has evolved into a refractive procedure where optimal visual outcomes depend not only on lens extraction but also on minimizing surgically induced astigmatism. Precise corneal incisions are widely used in phacoemulsification, yet the ideal incision site remains debated, particularly between superior and temporal approaches. Evidence from local populations remains limited, especially in low-resource settings. Objective: To compare surgically induced astigmatism following superior versus temporal clear corneal incision in patients undergoing phacoemulsification cataract surgery. Methods: This randomized controlled trial was conducted at the Department of Ophthalmology at Nishtar Hospital, Multan, from July to December 2024. A total of 66 patients aged 40–80 years scheduled for cataract surgery were enrolled and randomly allocated into two groups: superior precise corneal incision (n = 33) and temporal precise corneal incision (n = 33). All surgeries were performed by a single surgeon using a standardized stop-and-chop technique. Preoperative assessment included demographic data, visual acuity, and keratometry. Surgically induced astigmatism was measured using keratometry at one week postoperatively. Data were analyzed using SPSS version 25, with independent-samples t-tests used to compare outcomes between groups. Results: The overall mean age was 56.91 ± 10.84 years, with no significant differences in age or gender between groups. Baseline clinical and keratometric parameters were comparable. At 1 week postoperatively, mean surgically induced astigmatism was significantly lower in the temporal incision group (0.21 ± 0.14 D) than in the superior incision group (0.42 ± 0.18 D), with a mean difference of 0.21 D (95% CI: 0.13–0.29; p < 0.001). Stratified analysis demonstrated consistently lower astigmatism with the temporal approach across age, gender, and cataract duration subgroups. A higher proportion of patients in the temporal incision group developed minimal astigmatism (<0.25 D). Conclusion: Temporally precise corneal incision is associated with significantly less surgically induced astigmatism compared to superior incision following phacoemulsification. The temporal approach may offer superior early refractive outcomes and represents a preferable option for routine cataract surgery, particularly in resource-limited settings.